Load-deflection characteristics of coated and noncoated nickel-titanium wires in self-ligating brackets using a modified bending test: An in vitro study - Tripti Tikku; Rohit Khanna; Akhil Agarwal; Kamna Srivastava; Shashank Shekhar; Ivy Shukla (Wolters Kluwer Medknow Publications, 2019)
Background: To determine and compare the force-deflection values of different types of nickel-titanium (NiTi) wires during unloading phase at varying deflections, that is 1 mm, 1.5 mm, 2 mm, and 2.5 mm, with the use of self-ligating ceramic brackets using modified bending test on a typodont under controlled temperature conditions. Materials and Methods: In this in vitro study total of 45 wires of ovoid shape of three different NiTi wires - pseudoelastic NiTi (Group I), heat activated NiTi (Group II), and esthetic coated NiTi (Group III) for maxillary arch were tested after insertion in ceramic self-ligating brackets bonded to plastic teeth of phantom jaw . The maxillary left lateral incisor was removed to simulate a malpositioned tooth which acted as the load site, and load-deflection characteristics were measured during unloading using Instron, and data analyzed statically by two-way analysis of variance ,Tukey's post hoc test, intraclass correlation coefficient and Pearson correlation coefficient. A two-sided (α = 2) P < 0.05 was considered statistically significant. Results: When wires were compared at each deflection statistically significant difference was observed between the three groups of wires (Group I > Group II > Group III) at all the four levels of deflection except for Group II versus Group III at 1 mm, 1.5 mm, and 2 mm of deflection. Statistically significant difference was noted in mean load values for comparisons made at different deflections for each wire except for the comparison made at 1.5 versus 2 mm for Group II and Group III. Conclusion: Overall comparison showed esthetic coated Ni-Ti wires gave significantly lower mean load values, followed by heat activated and pseudoelastic NiTi wires. Thus, heat activated NiTi wires are best suited in patients with severe malpositions/periodontitis, while for esthetically conscious patients esthetic coated NiTi can be used.